2017
DOI: 10.1093/annonc/mdx710.006
|View full text |Cite
|
Sign up to set email alerts
|

In patients with advanced non-small cell lung cancer (NSCLC) LAG-3 is expressed on activated TILs and predicts resistance to PD-1 axis blockers

Abstract: Background: The functional role and clinical utility of measuring PD-1, LAG-3 and TIM-3 in NSCLC tumor tissue remain poorly understood even though corresponding clinical trials with blocking agents are ongoing. We analyzed the expression of these targets in association with key functional immune metrics and outcome after treatment with PD-1 axis blockers in human NSCLC. Methods: We performed CyTOF on immune cell suspensions from 20 primary human NSCLCs to map the distribution of PD-1, LAG-3 and TIM-3 and explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Increasing IFN-γ response is a current goal of pharmacological development to boost ICB, notably with STING (stimulator of interferon genes) agonist ( 88 ). Finally, there are limited data for alternative checkpoints such as LAG-3 expression on T cells, associated with shorter OS with PD-1 inhibitors ( 89 ). In conclusion, an approach combining both T cell exclusion and dysfunction [as the gene expression TIDE computational method ( 85 )] may be particularly relevant to predict ICB response.…”
Section: Baseline Predictors Of Responsementioning
confidence: 99%
“…Increasing IFN-γ response is a current goal of pharmacological development to boost ICB, notably with STING (stimulator of interferon genes) agonist ( 88 ). Finally, there are limited data for alternative checkpoints such as LAG-3 expression on T cells, associated with shorter OS with PD-1 inhibitors ( 89 ). In conclusion, an approach combining both T cell exclusion and dysfunction [as the gene expression TIDE computational method ( 85 )] may be particularly relevant to predict ICB response.…”
Section: Baseline Predictors Of Responsementioning
confidence: 99%
“…Some studies provided evidence that PD-1 could interact with TIM-3 and Gal-9 upregulated by inflammatory cytokines to attenuate apoptosis of T cells in cancers (Yang et al, 2021). The levels of PD-1 and TIM-3 protein were significantly correlated in non-small cell lung cancer, suggesting their interplay role in cancers (Datar et al, 2019). The level of TIM-3 is also a potential biomarker for anti-angiogenesis and immunotherapy to evaluate the therapeutic effect (Pignon et al, 2019;Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, multiple clinical trials investigate the therapeutic potential of combined CTLA4/PD-1 blockade in NSCLC patients (NCT03409614, NCT02453282, NCT03319316). Besides PD1 and CTLA4, LAG3 is another important immune checkpoint receptor that was found to be expressed on activated TILs but not NSCLC cells [ 31 ]. Preclinical studies have found that inhibition of LAG3 allowed cytotoxic T-cells to regain cytotoxic function similar to PD-1/PD-L1 inhibition [ 32 ].…”
Section: Discussionmentioning
confidence: 99%